2018
DOI: 10.1155/2018/4823130
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Temperature‐Control Measures for Concrete Structures: A Case Study of the Sluice Project

Abstract: Temperature control and crack prevention in sluice pier concrete is a key issue in the early design and construction period. Strong surface insulation may lead to cracks after formwork removal, while weak surface insulation may result in a high crack risk in the early age. e water-cooling measure may also cause severe cracks at a rapid cooling rate. erefore, the optimum temperature control scheme should be comparatively studied against the alternatives. In this paper, we investigate crack prevention in sluice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…It can be seen from the concrete heat conduction equation 4that the temperature change of a specified concrete is related to time and internal heat production, that is to say, for equation 4FORMATION OF TEMPERATURE CRACKS OF CONCRETE IN HIGH-RISE BUILDINGS... which is used for describing the temperature variation of a specified concrete, it has two unknowns numbers, t and in Q . There are innumerable solutions satisfying equation 4from the mathematical point of view, but the special value solution is needed in practical application; hence it is necessary to add initial and boundary conditions [9] to equation (4).…”
Section: Principle Of Heat Conductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen from the concrete heat conduction equation 4that the temperature change of a specified concrete is related to time and internal heat production, that is to say, for equation 4FORMATION OF TEMPERATURE CRACKS OF CONCRETE IN HIGH-RISE BUILDINGS... which is used for describing the temperature variation of a specified concrete, it has two unknowns numbers, t and in Q . There are innumerable solutions satisfying equation 4from the mathematical point of view, but the special value solution is needed in practical application; hence it is necessary to add initial and boundary conditions [9] to equation (4).…”
Section: Principle Of Heat Conductionmentioning
confidence: 99%
“…Therefore, measures need to be taken to prevent it. Huang [4] regarded the prevention of pier concrete cracks as a multifactor system optimization problem and studied the optimization method of pier concrete temperature control measures using uniform design method and neural network model. He found that pier concrete should adopt inner tube cooling and adopt reasonable surface insulation measures and low concrete pouring temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Such models usually include temperature component, hydraulic component, and aging component. Experiments demonstrate that temperature is crucial to control concrete deformation [2,3] and that variations in temperature are an important factor in determining the opening and closing of concrete cracks [4]. e temperature component is thus considerably sensitive to the temperature variations [1].…”
Section: Introductionmentioning
confidence: 99%
“…For small water conservancy projects, it is difficult to use temperature control measures such as aggregate precooling and ice mixing to control the temperature of concrete pouring due to economic factors. For thin-walled and massive concrete structures such as hydraulic tunnel linings, aqueducts, and small sluice floors, due to the large temperature gradient inside the structure and the constraints of the foundation or surrounding rocks, large thermal stresses will be generated [10,11]. e thickness of the structure is thin, so it is not easy to lay cooling water pipes, and the cost of measures to limit the cracks in the steel bar is high [12].…”
Section: Introductionmentioning
confidence: 99%